Ash and Ash-slag Waste as Multifunctional Raw Material - Kashkovsky, V.I.; Yevdokymenko, V.O.; Kamenskyh, D.S.; Tkachenko, T.V.; Vakhrin, V.V. (Science and Innovation, 2024)
The research deals with developing methods for the efficient use of ash and ash-slag waste, in particular, for fixation of municipal wastes (raw and digested sludge, redundant or deposited sediments), for obtaining of amorphous high-clean silicon dioxide; and for purification of circulating supernatant water of aeration stations.